The Debate on Globalization, Poverty, and Inequality : Why Measurement Matters - Ravallion, Martin (World Bank, Washington, DC, 2014)
In the last year or so, markedly different claims have been heard within the development community about just how much progress is being made against poverty and inequality in the current period of "globalization." Ravallion provides a nontechnical overview of the conceptual and methodological issues underlying these conflicting claims. He argues that the dramatically differing positions taken in this debate often stem from differences in the concepts and definitions used and differences in data sources and measurement assumptions. These differences are often hidden from view in the debate, but they need to be considered carefully if one is to properly interpret the evidence. The author argues that the best available evidence suggests that if the rate of progress against absolute poverty in the developing world in the 1990s is maintained, then the Millennium Development Goal of halving the 1990 aggregate poverty rate by 2015 will be achieved on time in the aggregate, though not in all regions. He concludes with some observations on the implications for the more policy-oriented debates on globalization and pro-poor growth.